Some school-based factors leading to the girls' high performance in science subjects at secondary school level - Kalikulali, Rachel Mpatadhuka W. (1998)
Thesis (M.A., Wom. Stud.) - Makerere University, 1998.
Includes bibliographical references (p.104-109)
Keywords: Science -- Study and teaching (Secondary).